2006
DOI: 10.1111/j.1525-139x.2006.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

HEMATOLOGY: ISSUES IN THE DIALYSIS PATIENT: Platelet Dysfunction and End‐Stage Renal Disease

Abstract: Patients with end-stage renal disease (ESRD) develop hemostatic disorders mainly in the form of bleeding diatheses. Hemorrhage can occur at cutaneous, mucosal, or serosal sites. Retroperitoneal or intracranial hemorrhages also occur. Platelet dysfunction is the main factor responsible for hemorrhagic tendencies in advanced kidney disease. Anemia, dialysis, the accumulation of medications due to poor clearance, and anticoagulation used during dialysis have some role in causing impaired hemostasis in ESRD patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
121
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(126 citation statements)
references
References 75 publications
3
121
0
2
Order By: Relevance
“…A history of CKD has been reported to be associated with increased risk for re-bleeding in previous studies [15, 17], and it was also a risk factor in our study. The possible mechanisms of bleeding in patients with CKD may be platelet abnormalities and platelet-vessel wall interaction [30, 31]. We also found that a history of CDB would be a risk factor.…”
Section: Discussionmentioning
confidence: 57%
“…A history of CKD has been reported to be associated with increased risk for re-bleeding in previous studies [15, 17], and it was also a risk factor in our study. The possible mechanisms of bleeding in patients with CKD may be platelet abnormalities and platelet-vessel wall interaction [30, 31]. We also found that a history of CDB would be a risk factor.…”
Section: Discussionmentioning
confidence: 57%
“…The limited quality and heterogeneity of available data mean that all we can reasonably conclude from current evidence is that the baseline incidence of major bleeding in hemodialysis patients is substantially higher than for the general population, and that antiplatelet and anticoagulant use increases this yet further. This is as expected, given that these patients are known to have both preexisting platelet dysfunction and a higher rate of invasive procedures [4]. …”
Section: Introductionsupporting
confidence: 54%
“…However, to the best of our knowledge, this is the first report demonstrating an independent relationship between HD and early death in ICH patients, adjusted for renal dysfunction. Maintenance HD patients have increased inflammatory activation [21] and disturbances of the coagulation system [22]. Inflammation and blood coagulation abnormalities are known to play a key role in early hematoma expansion and perihematoma brain edema after ICH [23].…”
Section: Discussionmentioning
confidence: 99%